PEMAHAMAN GURU PROPINSI JAWA TENGAH TERHADAP KEMAMPUAN MELIHAT DAN BERTANYA TENTANG REALITAS DALAM RANGKA PENERAPAN METODE PEMBELAJARAN ILMIAH - Harsono, Harsono (Jurnal Pendidikan Ilmu Sosial, 2015)
The publication paper title is â€œ Elementary school Teachers Knowing for see andquestion in Central Javaâ€. That is a part of researct publication. The reaserchlocation is Semarang, Demak, Kudus, and Pati teritorial. The problem statementof the paper are how long elementary school teachers knowed about capacityfor reality see and questions.Instrumen of research is questionary, there are any question about elementary school teachersknowed about capacity for reality see and elementary school teachers knowed about capacityfor reality questions. That is a quantitaive research and then survay research design.We get some information that level of capasity elementary school teachers knowed aboutcapacity for reality see and questions are low. That is consistent with other research result, whenwe get a same kinds.